Person-Organization Fit dan Organizational Citizenship Behavior Karyawan Bagian Produksi PT. X - Fikri, Harry Theozard; Rahmadani, Sari; Okfrima, Ria (Psyche 165 Journal, 2023)
Employees are a company's assets, and as employees they should always develop the resources they have. OCB is an important behavior that every employee must have in an effort to create the best work performance for a company. This research aims to see whether there is a relationship between person organization fit and organization citizenship behavior (OCB) in production employees at PT. The independent variable in this research is person organization fit and the dependent variable is organization citizenship behavior (OCB). The measuring instruments used in this research are the organization citizenship behavior (OCB) scale and person organization fit. The sampling technique in this research used a simple random sampling technique. The sample in this study was 84 production employees at PT. X. validity and reliability test in this study using the alpha cronbach technique where the results of the validity coefficient of the organization fitting coefficient moved from Rix= 0,357 to RIX= 0,726 with a reliability coefficient of α= 0,922 while on the scale of the organization citizenship from rix=0,331 to rix=0,753 with a reliability coefficient of α=0,943. Based on data analysis, a correlation value of 0,758 was obtained with a significance level of 0,000, which means the hypothesis was accepted. This shows that there is a positive and significant relationship between person. This shows that there is a positive and significant relationship between person organization fit and organization citizenship behavior (OCB) of production employees at PT. X. The contribution of the person organization fit variable to organization citizenship behavior (OCB) is 57%.